Organisational knowledge, innovative behaviour and organisational performance: the mediating role of knowledge management in SMEs’ service sector of Malaysia / Muhammad Khairul Ridzuan Mhd Sari - Mhd Sari, Muhammad Khairul Ridzuan (2022)
Small and Medium Enterprises (SMEs) contributes to the country’s economic growth by acting as the source of employment, promoting regional economic development and stability and fueling Gross Domestic Product (GDP) significantly. Nevertheless, the huge potential for the SME market is not reflected in their growth and sustainability where the mass numbers do not project their true capabilities. Factors that influence SMEs’ performance remain debatable where no true consensus is achieved to enlighten the issue. Despite much external assistance from the private and government sectors, a question arises on the SMEs’ capabilities to leverage the available resources. Looking at the issue through the lens of Resource-Based View (RBV) and Knowledge-Based View (KBV), this study attempted to examine the influence of the firm’s internal factors, which is organisational knowledge as the predictors of SMEs’ performance. However, some literature states its limitations. To further uncover the issue, this study incorporates Resource Orchestration Theory (ROT) to support the newly developed model to examine organisational knowledge that comprises intellectual capital, knowledge management, and absorptive capacity towards the SMEs’ performance through the role of innovative behaviour in SMEs of Malaysia. On top of that, this study also examines knowledge management as a mediating variable in the relationship between intellectual capital with innovative behaviour and SMEs’ performance. This research applies a positivist paradigm where a quantitative approach was selected to gather the information from the respondents based on the established sample size through G-POWER software. By applying the non-probability sampling technique, the study seeks answers from the respondents through purposive sampling, where 144 completed responses were collected and analysed using PLS-SEM software, SmartPLS 3.3.3, to conclude the findings as desired by the research objectives and hypotheses. The findings suggested that intellectual capital has a significant relationship with SMEs’ performance. The same results also applied to the relationship between intellectual capital and knowledge management, intellectual capital and absorptive capacity, knowledge management and innovative behaviour, knowledge management and SMEs’ performance, and last but not least innovative behaviour and SMEs’ performance. However, the result indicates that intellectual capital and absorptive capacity do not significantly influence innovative behaviour. The finding also proves that knowledge management fully mediates the relationship between intellectual capital and innovative behaviour and partially mediates the relationship between intellectual capital and SMEs’ performance. This research adds to the body of knowledge related to organisational knowledge and innovative behaviour by introducing a new model for assessing factors that influence organisational performance, particularly for SMEs constrained by the liability of smallness and newness in moving forward to achieve superior performance. Future studies are also recommended to explore the nexus between resource availability in terms of tangible or intangible assets and steering mechanisms such as leadership or entrepreneurial skills to optimise the available resources